Pengaruh Latihan Jantung Paru Terstruktur Pada Tenaga Kesehatan Dengan Sindroma Pasca COVID – 19 Terhadap Peningkatan Kapasitas Fungsional - Teuku Heriansyah; Muhammad Ridwan; Nina Widasari (LITBANG RSUDZA, 2021)
COVID-19 is a multisystem disease, with various complications besides respiratory disorders that can affect various systems ranging from the heart, kidneys, gastrointestinal, nervous, endocrine, and musculoskeletal. Post COVID-19/Long Covid Syndrome is a condition where the symptoms of COVID-19 persist even though they have been declared cured. Health workers have a fairly large risk of being infected with COVID-19, as well as the risk of symptoms of Post COVID 19 Syndrome with the most complaining symptom being fatigue. The purpose of this study was to examine the effect of supervised cardiopulmonary exercise on increasing functional capacity in health workers with Post Covid-19 Syndrome. This study used an experimental research design with the sample divided into the control group and the treatment group. We provided supervised cardiopulmonary exercise with moderate and high intensity on 30 medical personnel for 12 times in Cardiac Rehabilitation Gymnasium. It was concluded that treatment group experienced an increase in functional capacity compared to the control group. The improvement in functional capacity between the moderate and high intensity exercise groups was not significantly different. Increased functional capacity will improve the quality of life in patients with Post Covid-19 Syndrome.